2015
DOI: 10.1007/s11269-015-0948-4
|View full text |Cite
|
Sign up to set email alerts
|

A Management Analysis Tool for Emancipated and Public Irrigation Areas Using Neural Networks

Abstract: The management transfer of irrigation districts from the public to the private sector became a broad strategy throughout the world. Although the extent to which the process is being implemented, there is little information available on the results of these transfer programs. In addition, there is no established procedure to analyze economic feasibility and general performance of the irrigation districts. In this context, the aim of this research was to develop a model to evaluate the performance of self-manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Sprinkler and localized systems performed similarly and much better than the surface system (Figure 3). The superiority of the two pressurized systems vs. surface irrigation was expected and in consonance with the results in other regional comparative assessments (Gonçalves et al, 2015). However, Serra-Wittling et al (2019) reported that in all the French experiments comparing localized with sprinkler systems, the former never used more water than the latter, and in most experiments it used significantly less.…”
Section: Discussionsupporting
confidence: 76%
“…Sprinkler and localized systems performed similarly and much better than the surface system (Figure 3). The superiority of the two pressurized systems vs. surface irrigation was expected and in consonance with the results in other regional comparative assessments (Gonçalves et al, 2015). However, Serra-Wittling et al (2019) reported that in all the French experiments comparing localized with sprinkler systems, the former never used more water than the latter, and in most experiments it used significantly less.…”
Section: Discussionsupporting
confidence: 76%
“…Technology for measuring the actual amount of water supplied to secondary canals and farms is becoming more common (Lozano and Mateos, 2008), helping to reduce non‐consumptive use and allowing better‐adjusted water delivery schedules (Clemmens and Bos, 1990). In addition, at farm level, promoting the use of pressurized irrigation systems, where viable, should reduce some of the losses that occur under surface irrigation (Gonçalves et al ., 2015). These kinds of improvement could facilitate the adjustment of the water supply to the evapotranspiration plus the leaching requirements and, indirectly, to close crop yield gaps.…”
Section: Discussionmentioning
confidence: 99%
“…surface irrigation in CPIS. In turn, Gonçalves et al (2015) attributed the poor performance of CPIS to the on-farm irrigation method. Moreover, the delivery and maintenance service initially provided by CPIS was drastically reduced in the 1980s.…”
Section: Discussionmentioning
confidence: 99%